Bronchiolitis, respiratory syncytial virus, and recurrent wheezing: what is the relationship? - Fonseca,Claudia de Brito (2003)
Various follow-up studies of children hospitalized with bronchiolitis caused by respiratory syncytial virus have demonstrated that a significant proportion of infants (50%) have recurrent wheezing during childhood. Nevertheless, the relationship between these two entities, if any, has not been established. In order to explain this observation, several hypotheses have been proposed. The first suggests that some children could have an individual predisposition to bronchiolitis caused by respiratory syncytial virus and recurrent wheezing. The virus could be a marker of this condition, and the individual predisposition could in turn be related to an individual hypersensitivity to common allergens (atopy), airway hyperreactivity, or to some disorder related to pulmonary anatomy or physiology that was present before the acute episode of bronchiolitis. Another hypothesis proposes that respiratory syncytial virus could be directly responsible for recurrent wheezing. During an episode of bronchiolitis, the damage in the airway mucosa caused by the vital inflammatory response to infection contributes to sensitivity to other allergens or exposes irritant receptors, resulting in recurrent wheezing. For this review, we analyzed the studies that discuss these hypotheses with the purpose of clarifying the mechanisms for the important issue of recurrent wheezing in childhood.